Ryby : dary rzek i morz - Grieser, Ludwig; Grieser, Ludwig (Warszawa : Warszawski Dom Wydawniczy, 1992)
Recipes for freshwater and saltwater fish.
Includes index.
Translation of: Fisch frischer fang aus fluss und meer.
Keywords: Cooking (Fish)